Continuities and Discontinuities in Post-Apartheid Parenting in South Africa - Mpofu, Phumuzani; Mayisela, Simangele (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2026)
This study explores the continuities and discontinuities in post-apartheid parenting in South Africa, examining how colonial and apartheid legacies continue to shape family life while intersecting with contemporary social, economic, and cultural changes. Guided by postcolonial theory and a transformative paradigm, the research employed a qualitative case study design, engaging 30 participants, including young adults, parents, and professionals involved in child-rearing. Data were generated through focus group discussions and semi-structured interviews, then analysed thematically to identify enduring and emergent parenting practices. Findings reveal that traditional communal values, moral instruction, and relational care rooted in Ubuntu persist alongside evolving norms shaped by children’s rights legislation, urbanization, globalization, and digital media exposure. Disciplinary practices, gender roles, and parental authority reflect both intergenerational continuities and negotiated adaptations, with tensions arising between preserving cultural norms and embracing rights-based, democratic approaches. Participants highlighted hybrid parenting strategies that blend indigenous values with contemporary developmental frameworks and emphasized the importance of schools, religious institutions, and community structures in supporting child-rearing. The study underscores the need for a uniquely South African parenting model that harmonizes Ubuntu-based principles with modern notions of child autonomy, positive discipline, and social responsibility. By documenting how history, culture, and socio-political transformation intersect in parenting, this research provides insights for policymakers, educators, and practitioners seeking to strengthen culturally grounded and contextually responsive family practices in post-apartheid South Africa.